Memories, material culture, and methodology: employing multiple filmic formats, forms, and informal archives in anthropological research among Zimbabwean migrant women - Horn, Roger (Gender Studies, 2019)
This dissertation offers two components: the first, a written thesis, is focused on memories, material culture, and methodology in the representation of female Zimbabwean migrants in Cape Town, South Africa. The second component comprises four films, which utilize multiple unconventional methodological approaches including split-screen presentation, found footage filmmaking, and combined film and digital footage in order to contribute to knowledge of the long-term transnational migrant experience through a sensory examination of memories and material culture in both South Africa and Zimbabwe. Since gaining independence in 1980, Zimbabwe has faced many challenges as the result of poor economic and political decisions carried out by recently ousted former President Robert Mugabe and his ZANU-PF political party, amplified by international sanctions and corruption. The problems within Zimbabwe have led to approximately 25% of its population leaving the country, many of whom have migrated to Zimbabwe’s long-time ally South Africa. This mass movement of people has resulted in profound effects upon the region as many Zimbabweans arrive in an unwelcoming South African society and face multiple challenges including obtaining work permits and jobs, and are often the victims of xenophobic verbal and physical abuse, with multiple reports revealing that 90% or more of these migrants remitted to family members in Zimbabwe who were dependent upon remittances for survival (von Burgsdorff, 2012:15). Through my engagement with traditional ethnographic research methods, unconventional visual research methods, and working with informal archives, such as found 8mm footage, Super 8mm footage, and YouTube videos I have spent four years researching the crossroads of memories and material culture in Zimbabwe and South Africa. I produced four films to accompany this written thesis, each of which emerged from sustained analysis of my material, reflections upon the form and content, and gathering feedback from my interlocutors during and after the assembly of each film. In addition to contributing to an understanding of the role memories and material culture serve in the lives of the women with whom I worked to produce this work, this dissertation seeks to provide new ways to envision an engagement with visual media to convey the complexity of migrants’ daily lives.